Procedural guarantees for public participation in environmental protection. - Folgier, Anna (Polish Yearbook of Environmental Law, 2020)
This article analyses the principles and the procedure related to public participation in environmental protection within the meaning of the Act of 3 October 2008 on the Provision of Information about the Environment and its Protection, Public Participation in Environmental Protection and Environmental Impact Assessment. This Act provides for a division of public participation into: public participation in decision making (Art. 33-38) and public participation in the preparation of documents (Art. 39-43). The author describes one by one the solutions that ensure public participation in procedures in individual matters settled by way of administrative decisions, and the solutions that ensure public participation in the process of preparing documents for which this participation is obligatory. In conclusion, the author presents specific rights of environmental organisations related to public participation, as environmental organisations, by referring to their statutory objectives and declaring their willingness to participate in procedures requiring public participation, participate in these procedures as a party.